Analysis of the transient body effect model for an LTPS TFT on a plastic substrate. (January 2021) - Choi, Yunyeong; Lee, Taekyeong; Park, Jisun; Shin, Hyungsoon
Highlights: Transient current variation of flexible thin film transistor on Polyimide substrate. Device simulation of movable ion distribution in Polyimide under the operating bias. Threshold voltage shift resulted from transient body effect as varying body potential. Circuit model fitting the long and short term trends of transient body effect well. Abstract: This work investigates the transient current in the subthreshold region of a low-temperature polycrystalline silicon thin-film transistor (LTPS TFT) on a polyimide (PI) substrate. The measurement of this current shows an instability that is not seen in the device on a glass substrate; the instability appears as a current variation under constant voltage and overshoot or undershoot under external stress voltage transitions. To explain this effect for a TFT on a PI substrate, a transient body effect (TBE) is suggested due to a threshold voltage shift caused by the charge distribution inside the substrate. A SPICE model is proposed based on this concept, and it shows excellent agreement with device measurements. The model offers a simulation guideline for LTPS TFTs on PI substrates.